2017
DOI: 10.1002/cncr.30722
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer stage variation and survival in association with insurance status and sociodemographic factors in US women 18 to 64 years old

Abstract: Insurance status at diagnosis and sociodemographic factors are associated with breast cancer mortality. Factors underlying these associations warrant further study. Cancer 2017;123:3125-31. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 34 publications
5
68
2
Order By: Relevance
“…On the other hand, insurance status has recently shown to be a particularly important part of social support. For example, Hsu et al showed that insurance status at diagnosis is associated with breast cancer mortality and Walker et al found that uninsured patients with the ten most deadly cancers were more likely to have worse survival outcomes [4,20]. One of the main explanations is that insured patients can afford the expense of complying with medical recommendations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, insurance status has recently shown to be a particularly important part of social support. For example, Hsu et al showed that insurance status at diagnosis is associated with breast cancer mortality and Walker et al found that uninsured patients with the ten most deadly cancers were more likely to have worse survival outcomes [4,20]. One of the main explanations is that insured patients can afford the expense of complying with medical recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to marital status, a number of studies have reported that uninsured and Medicaid insured patients with breast, colorectal, cervical, lung, or head and neck cancer have either higher mortality or lower survival outcomes than do patients with private insurance, even after adjusting for other factors [4][5][6][7]. From a clinical perspective, patients without insurance have much more difficulty in obtaining adequate treatment for their condition, potentially delaying adjuvant therapy, receiving less than the standard dose of chemotherapy, and increasing their mortality risk.…”
Section: Introductionmentioning
confidence: 99%
“…To build our model for survival analyses, we chose to include all clinically relevant variables known to have a meaningful association with survival in prior cancer studies. 16,17 Final models were checked for proportional hazards assumption through log-log plots of survival, as well as for interaction effects. We decided to not include radiotherapy in multivariable survival analysis given the lack of detail in SEER regarding both chemotherapy and radiation dosing, schedule, and adherence, which may significantly impact treatment outcomes in patients with anal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariable Cox proportional hazards models were used to evaluate the effect of MHI and clinically relevant variables (age, sex, race, marital status, stage of disease, tumor grade, and year of diagnosis) on CSS and OS. To build our model for survival analyses, we chose to include all clinically relevant variables known to have a meaningful association with survival in prior cancer studies . Final models were checked for proportional hazards assumption through log‐log plots of survival, as well as for interaction effects.…”
Section: Methodsmentioning
confidence: 99%
“…4,5 Reduced access to care experienced by uninsured patients puts them at increased risk of advanced-stage disease at diagnosis and worse overall survival. [4][5][6][7] This study was conducted to investigate the influence of insurance status on postoperative surgical complications in gynecologic cancer patients treated at a large tertiary-care center in North Carolina. Recognizing the association between insurance status and surgical outcomes at a large state hospital where care is provided regardless of a patient's ability to pay could provide insight into the national implications of a single-payor model.…”
Section: Introductionmentioning
confidence: 99%